The Clinical, Myopathological, and Genetic Analysis of 20 Patients With Non-dystrophic Myotonia - Wang, Quanquan; Zhao, Zhe; Shen, Hongrui; Bing, Qi; Li, Nan; Hu, Jing (Frontiers in Neurology, 2022)
Introduction Non-dystrophic myotonias (NDMs) are skeletal muscle ion channelopathies caused by CLCN1 or SCN4A mutations. This study aimed to describe the clinical, myopathological, and genetic analysis of NDM in a large Chinese cohort. Methods We reviewed the clinical manifestations, laboratory results, electrocardiogram, electromyography, muscle biopsy, genetic analysis, treatment, and follow-up of 20 patients (from 18 families) with NDM. Results Cases included myotonia congenita (MC, 17/20) and paramyotonia congenita (PMC, 3/20). Muscle stiffness and hypertrophy, grip and percussion myotonia, and the warm-up phenomenon were frequently observed in MC and PMC patients. Facial stiffness, eye closure myotonia, and cold sensitivity were more common in PMC patients and could be accompanied by permanent weakness. Nine MC patients and two PMC patients had cardiac abnormalities, mainly manifested as cardiac arrhythmia, and the father of one patient died of sudden cardiac arrest. Myotonic runs in electromyography were found in all patients, and seven MC patients had mild myopathic changes. There was no difference in muscle pathology between MC and PMC patients, most of whom had abnormal muscle fiber type distribution or selective muscle fiber atrophy. Nineteen CLCN1 variants were found in 17 MC patients, among which c.795T>G (p.D265E) was a new variant, and two SCN4A variants were found in three PMC patients. The patients were treated with mexiletine and/or carbamazepine, and the symptoms of myotonia were partially improved. Conclusions MC and PMC have considerable phenotypic overlap. Genetic investigation contributes to identifying the subtype of NDM. The muscle pathology of NDM lacks specific changes.